Alternative Representation for the Stability Diagram of Quadrupole Ion Traps upon Additional Quadrupolar Excitation. Issue 3 (June 2013) - Vernier, Arnaud; Chirot, Fabien; Antoine, Rodolphe; Salvador, Arnaud; Charrier, Jean-Philippe; Lemoine, Jerome; Dugourd, Philippe
We present a combined theoretical and experimental study of the stability of ions in a linear ion trap under the application of one or two auxiliary radiofrequency (RF) fields, in order to perform simultaneous resonant excitation/ejection of several different ions. The influence of the amplitude and frequency of the auxiliary field is addressed through the construction of experimental and theoretical stability diagrams. Theoretical diagrams are constructed using the method developed by Konenkov et al . [ J. Am. Soc. Mass Spectrom . 13, 597 (2002)]. We propose a new representation of stability diagrams more adapted to the study of auxiliary excitations than the canonical one. Stability regions are represented as a function of the fundamental RF amplitude and of the relative intensity of the excitation. This representation facilitates the monitoring of the evolution of the mass-selectivity of first- and higher-order resonant excitations in the trap, for which an empirical law is derived. We also show that the relative phase shift between the excitation field and the main driving field has a strong influence on the shape of the diagrams.